Challenging Glass 4 & COST Action TU0905 Final Conference : proceedings of the Challenging Glass 4 & COST Action TU0905 Final Conference, Ecole polytechnique fédérale de Lausanne (EPFL), Lausanne, Switzerland, 6-7 February 2014 /: proceedings of the Challenging Glass 4 & COST Action TU0905 Final Conference, Ecole polytechnique fédérale de Lausanne (EPFL), Lausanne, Switzerland, 6-7 February 2014. ([2014]) - Unknown
No abstract available